PHYSICAL AND CHEMICAL CHARACTERIZATION OF SOIL UNDER DIFFERENT USES IN WATERSHED - da Cunha Kemerich, Pedro Daniel; Martins, Sérgio Roberto; Kobiyama, Masato; Buriol, Galileo Adeli; Rizzardi, Alencar Simão; da Silva, Régis Leandro Lopez; de Borba, Willian Fernando (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2012)
The soil has become an essential resource for the survival of human beings, but with the increasing levels of contamination generated by human actions, this resource is getting all this pollution load resulting in changes in their properties. Based on that, this study aimed to characterize the physical and chemical properties of soil under different uses in the Watershed of the Vacacaí-Mirim river. The clay content ranged from 8 to 51% with a mean of 28,84 ± 12,18%, the concentration of potassium ranged from 0,8 to 208 mg kg-1, with a mean of 54,56 ± 47,16 mg kg-1. The values of organic matter ranged from 0,6 to 2,9%, with a mean of 1,50 ± 0,63%, the concentration of phosphorus ranged from 0,7 to 6 mg kg-1 with a mean of 2,36 ± 1,52 mg kg-1, the pH values ranged from 4,2 to 5,8 with a mean of 4,76 ± 0,39. Among the analyzed parameters, we highlight the high levels of clay and organic matter in soils that are where the use is native forest and native field, being possible to say that the preservation of the soil contributes to the maintenance of these parameters. Among the chemical attributes, the highest concentrations are related to soils that have undergone human action, such as the ones grown with rice and soybean and the places used as pasture.